Assessing Lean Thinking in Hospital: A Conceptual Framework - O, Yancy; Ayuningtyas D (HM Publisher, 2024)
Currently, the lean thinking system has not been implemented in all hospitals in Indonesia, where there is a lot of waste that affects the low quality of service and patient safety. The aims of this study is to develop a conceptual framework as a basis for quantitative assessment of lean thinking systems in Indonesian Hospitals to improve services, increase patient satisfaction and improve hospital quality. In preparing the conceptual framework for the quantitative assessment model of the lean thinking system index, a literature study was carried out through a literature search for journals from several countries and textbooks using the keywords